Optimalisasi Program Posyandu Lansia dalam Meningkatkan Kesehatan di Desa Ngepung Kecamatan Kedamean Kabupaten Gresik - Muhamad Yusuf; Zainal Fatah; Kresna Adhi Prahmana (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
Optimizing the Elderly Posyandu (Integrated Healthcare Post) Program in Ngepung Village, Kedamean District, Gresik Regency, is a strategic step to improve the health and well-being of the elderly amidst the surging number of older adults in Indonesia. This research employs a descriptive qualitative approach, with data collected through purposive sampling involving Posyandu cadres, village officials, community health center staff, active elderly participants, and their accompanying family members. The findings reveal that program implementation faces challenges such as low elderly participation, limited facilities and healthcare personnel, and a lack of awareness among the community and families. Mobility constraints and geographical access further exacerbate the suboptimal participation of the elderly. To overcome these obstacles, proactive strategies have been implemented, including door-to-door outreach, the formation of RT/RW (neighborhood/community unit)-based groups, and capacity building for cadres through training. This approach has been effective in increasing participation and expanding health services. The program's success is also supported by cross-sectoral collaboration and the active involvement of the village government, community leaders, religious organizations, and universities. Sound village policies and appropriate budget allocation are crucial for the sustainability of these activities, as is cooperation with community organizations and Corporate Social Responsibility (CSR) initiatives from nearby companies. Furthermore, diversifying activities such as routine check-ups, health education, elderly exercise, and supplementary feeding has been able to boost the motivation of older adults. Strengthening the role of cadres and educating families on assisting the elderly are also key to success. Data and case studies demonstrate that optimization success depends not only on physical aspects and resources but also on social aspects, such as community awareness and family involvement. Overall, the collaboration of all community components and the village government, along with appropriate strategies and improved facilities, are the main factors in enhancing the health and quality of life of the elderly in Ngepung Village.